Introduction: Enabling Large‐Scale Computational Science—Motivations, Requirements, and Challenges - Parashar, Manish; Li, Xiaolin (Advanced Computational Infrastructures for Parallel and Distributed Adaptive Applications, 2009)
This chapter contains sections titled: Motivation Requirements and Challenges A Taxonomy for Adaptive Applications and Management Strategies A Conceptual Architecture for Computational Infrastructures Overview of the book References